Behavior of Mortar Samples with Waste Brick and Ceramic Under Freeze-Thaw Effect - Kaplan, Gökhan; Yilmazoğlu, Mehmet Uğur; Yaprak, Hasbi̇; Mütevelli̇, İffet Gamze; Memi̇ş, Selçuk (Springer International Publishing, 2018)
Increasing number of industrial facilities and population concentration in particular regions along with overconsumption are main reasons of the increased environmental pollution. It is a necessity to preserve available resources and to keep the waste in control in order to achieve a sustainable development goal. In recent years, concepts of waste management, recycling and sustainability have gained importance with regards to the construction industry. Today, approximately 35 billion tons of concrete is produced worldwide and 80% of this amount consists of aggregated manufactured using natural resources. A significant environmental impact is the case even for the production of cement, a binding agent for concrete, which accounts for 1 ton CO2 emission in order to produce 1 ton of cement. The main subject of this study is the production of a sustainable construction material with the use of ceramic instead of both aggregate and cement. Clay is defined as a common natural material with fine-grains, with layers and a high water absorption capacity. Ceramic products are construction materials which can replace cement generally in the form of artificial puzzolana. The main subject of this study is the use of the waste obtained from ceramic plants which produces ceramic products in mortars. Taguchi L9 array design was used as part of this experimental study. Water-binder ratio was set to 0.50 in the preparation of the mixes and natural aggregates were used. Aggregates were then replaced by pieces ceramic and brick at a percentage between 20 and 60% while cement was replaced by ceramic and brick powder at a percentage between 10 and 30%. The mixes were then subjected to freeze and thaw tests at 30, 60 and 90 cycles in accordance with ASTM C 666 standard. Dynamic modulus and mechanical properties of the mortars subjected to f-t effect were then identified. When the results of the tests were examined, it was found that the compressive strength at 7th and 28th days were decreased with the increase of the volume of ceramic and brick powder used while it was found that the use of ceramic and brick powder did not have a significant effect on the compressive strength at the 90th day. The use of ceramic and brick aggregate led to favorable results in terms of freeze-thaw resistance. Especially the use of 10% ceramic [(whiteware) CA] and 20% other ceramic [(brick) BA] aggregate in mortars subjected to 90 f-t cycles increased the dynamic modulus while similar results were found for the use of 5% ceramic powder and 10% brick powder in mortars subjected to 90 days of f-t cycles. This study shows that waste material obtained from ceramic and bricks industry can be repurposed in the construction industry.
Keywords: 13. Climate action; 9. Industry and infrastructure; 11. Sustainability; 7. Clean energy; 6. Clean water; 12. Responsible consumption